Use of hormonal contraceptives and occurrence of pregnancy-related pelvic pain: a prospective cohort study in Norway - Weiderpass Elisabete; Kumle Merethe; Alsaker Elin; Lund Eiliv (BMC, 2004)
Abstract Background Pregnancy-related pelvic pain is a common condition, and use of hormonal contraceptives before pregnancy has been proposed as a risk factor. We used data from a sub-sample of women participating in the "Norwegian Women and Cancer study" (NOWAC) to assess the association between hormonal contraceptive use and pelvic pain in pregnancy. Methods From a sub-group of 2078 parous women participating in the NOWAC study, information was collected from a self-instructive four-page questionnaire containing questions about lifestyle and medical conditions. We calculated odds ratios (OR) and 95% confidence intervals (CI), using unconditional logistic regression. Results In this study, the prevalence of pelvic pain in women was 26.5% during the first pregnancy and increased with parity. Use of hormonal contraceptives before a woman's first pregnancy was associated with an increased risk of pelvic pain in her first pregnancy (OR = 1.6; 95% confidence interval 1.2-2.2). There was no association between use of hormonal contraceptives and pelvic pain in the second or third pregnancy. Occurrence of pelvic pain in a previous pregnancy was the only factor associated with pelvic pain in subsequent pregnancies (OR = 51.1; 95% CI 32.9-79.5 in the second pregnancy and OR = 28.3; 95% CI 15.4-53.1 in the third pregnancy). Conclusion Use of hormonal contraceptives was associated with an increased risk of pelvic pain in a woman's first pregnancy. The most important determinant of pelvic pain in the second or third pregnancy was the history of pelvic pain in the preceding pregnancy.